Strongly enhanced Raman scattering of Cu-phthalocyanine sandwiched between graphene and Au(111). Issue 4 (19th December 2016) - Lin, Wan-Ing; Gholami, Mohammad Fardin; Beyer, Paul; Severin, Nikolai; Shao, Feng; Zenobi, Renato; Rabe, Jürgen P.
Abstract : Graphene and flat gold have both been argued to enhance Raman scattering of molecular adsorbates through a chemical mechanism. Here we show that these two effects can add to each other. Abstract : Graphene and flat gold have both been argued to enhance Raman scattering of molecular adsorbates through a chemical mechanism. Here we show that these two effects can add to each other. For Cu-phthalocyanine in between graphene and Au(111) on mica a Raman enhancement up to 68-fold has been observed.